2019
DOI: 10.1088/1361-651x/ab3294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different crystal orientations on the surface integrity during nanogrinding of monocrystalline nickel

Abstract: During nanofabrication, the processing of different crystal faces along the surface of a workpiece varies because of size effects. The burr height and subsurface damage during nanogrinding of different crystal orientations in monocrystalline nickel are simulated by molecular dynamics in this study. The burr height and depth of the subsurface deformation layer are calculated quantitatively by atomic displacement, common neighbor analysis and dislocation analysis techniques. Among the directions considered in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Yang et al [22] established a single crystal germanium nano-cutting model by MD method, studied the phase transformation and crystal structure evolution during multiple cutting, and pointed out that multiple cutting under the same machining parameters can improve the surface quality of the workpiece better than single cutting. Ren et al [23] used MD method to simulate repetitive nano-machining of single crystal nickel, analyzed cutting force, subsurface damage and surface topography during repetitive nanomachings, and found that repetitive machining at one time would reduce tool forces and improve material subsurface quality, while subsequent repetitive machining had little impact. Zhou et al [24] established the polycrystalline MD model of alloy tool steel with Fe, Cr and W to study the influence of tool geometry on the machining mechanism of alloy tool steel in the process of ultra-precision turning.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [22] established a single crystal germanium nano-cutting model by MD method, studied the phase transformation and crystal structure evolution during multiple cutting, and pointed out that multiple cutting under the same machining parameters can improve the surface quality of the workpiece better than single cutting. Ren et al [23] used MD method to simulate repetitive nano-machining of single crystal nickel, analyzed cutting force, subsurface damage and surface topography during repetitive nanomachings, and found that repetitive machining at one time would reduce tool forces and improve material subsurface quality, while subsequent repetitive machining had little impact. Zhou et al [24] established the polycrystalline MD model of alloy tool steel with Fe, Cr and W to study the influence of tool geometry on the machining mechanism of alloy tool steel in the process of ultra-precision turning.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that meeting these requirements was possible through the use of a new method and new tools. Conclusions came from the resent investigations on the features of abrasive tools [3,8,19,20], process kinematics [21], the influence of the processed material properties on the process results [22][23][24][25][26] and cutting fluid [9,27]. In the assumptions for the new method, the developed methodology of process monitoring [28,29], a thorough analysis of the properties of abrasive tools [30][31][32], and the topography of the treated surfaces [33] were used.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of grinding depth and abrasive grain diameter led to an increase of stacking faults and dislocations, whereas the size of the subsurface damage layer was found to be almost unaffected by the grinding speed. The same scientific group, in a later study [ 23 ] investigated the effect of crystal orientation in the case of nanocrystalline nickel. After they carried out simulations for six different crystal orientations, they showed that burr height was minimum at (110)[ 10] direction, whereas the deformed layer depth was minimum at (111)[ 10] direction.…”
Section: Introductionmentioning
confidence: 99%